Tunable Quantum Dots from Atomically Precise Graphene Nanoribbons Using a Multi‐Gate Architecture. (2nd February 2023) - Zhang, Jian; Braun, Oliver; Barin, Gabriela Borin; Sangtarash, Sara; Overbeck, Jan; Darawish, Rimah; Stiefel, Michael; Furrer, Roman; Olziersky, Antonis; Müllen, Klaus; Shorubalko, Ivan; Daaoub, Abdalghani H. S.; et al.
Abstract: Atomically precise graphene nanoribbons (GNRs) are increasingly attracting interest due to their largely modifiable electronic properties, which can be tailored by controlling their width and edge structure during chemical synthesis. In recent years, the exploitation of GNR properties for electronic devices has focused on GNR integration into field‐effect‐transistor (FET) geometries. However, such FET devices have limited electrostatic tunability due to the presence of a single gate. Here, on the device integration of 9‐atom wide armchair graphene nanoribbons (9‐AGNRs) into a multi‐gate FET geometry, consisting of an ultra‐narrow finger gate and two side gates is reported. High‐resolution electron‐beam lithography (EBL) is used for defining finger gates as narrow as 12 nm and combine them with graphene electrodes for contacting the GNRs. Low‐temperature transport spectroscopy measurements reveal quantum dot (QD) behavior with rich Coulomb diamond patterns, suggesting that the GNRs form QDs that are connected both in series and in parallel. Moreover, it is shown that the additional gates enable differential tuning of the QDs in the nanojunction, providing the first step toward multi‐gate control of GNR‐based multi‐dot systems. Abstract : The device integration of 9‐atom wide armchair graphene nanoribbons (GNR) into a multi‐gate field‐effect transistor geometry is reported. Low‐temperature transport spectroscopy measurements reveal quantum dot (QD) behavior with rich Coulomb diamond pattern. It is shown that the additional gates enable differential tuning of the QDs in the nanojunction, providing the first step toward multi‐gate control of GNR‐based multi‐dot systems.